Design and Analysis of CFRP Composite Multilayer High Pressure Vessels: A study on the design and analysis of CFRP composite multilayer high pressure vessels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The key objective of this paper is to structure and examine multilayer high pressure vessels and the highlights of multilayered high pressure vessels, their focal points over mono square vessel are talked about and burst pressure investigation of CFRP composite pressure vessels for different fiber direction edges.